Aseptic Meningitis and White Matter Disease in Childhood-Onset Neuropsychiatric Lupus - Mei Lam Hsu; Kwai Yu Winnie Chan (Case Reports in Rheumatology)
We reported a 10-year-old girl who had an atypical demyelinating disease as the presentation of her neuropsychiatric lupus. The patient had a 4-year history of systemic lupus erythematosus which had been on remission until she presented with fever and headache at the age of 10 years. Physical examination showed meningism. Extensive microbiological workup for infective meningitis was unrevealing. There was a radiographic finding of an extensive white matter hyperintensity on the magnetic resonance imaging (MRI) of the brain. At the initial stage of our case, as it was difficult to differentiate between infection of the central nervous system and neuropsychiatric manifestation of lupus, a course of intravenous immunoglobulin was given empirically instead of high-dose corticosteroid while awaiting the microbiological workup results. The fever and headache subsided shortly after commencement of intravenous immunoglobulin without use of pulse corticosteroid. After the active neurological symptoms remitted, she was given a total of six monthly doses of intravenous immunoglobulin at 2 g/kg/cycle and six biweekly doses of intravenous cyclophosphamide at 500 mg/m2/month. Interval MRI showed resolution of the white matter hyperintensity. Despite the extensive demyelinating disease on initial presentation, she remitted successfully without residual neurological sequelae.